PENGARUH FINANCIAL DISTRESS, KONEKSI POLITIK DAN FOREIGN ACTIVITY TERHADAP TAX AVOIDANCE - Yudawirawan, Moh. Yuddy; Yanuar, Yayan; Hamdy, Syaibatul (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this study was to examine and obtain empirical evidence of the effect of financial distress, political connections, and foreign activity on tax avoidance. This research was conducted using secondary data and then processed using the SPSS application program. The sample used in this study amounted to 11 mining companies that have been selected using a purposive sampling method that has met the criteria of 49 publicly traded companies listed on the Indonesia Stock Exchange for the period 2016-2019. The results of research on financial distress have a significant negative effect, while other variables (political connections, and foreign activity) do not have a significant effect on tax avoidance.